2019
DOI: 10.1186/s12889-019-6957-0
|View full text |Cite
|
Sign up to set email alerts
|

An online survey of users of tobacco vaporizers, reasons and modes of utilization, perceived advantages and perceived risks

Abstract: Background Tobacco vaporizers heat tobacco without burning it, to produce an inhalable aerosol. Various models have recently appeared on the market, mostly manufactured by the tobacco industry, but few of the studies published on tobacco vaporizers are independent from the manufacturers. The goals of this study were to explore who uses tobacco vaporizers, how these products are used, reasons for utilization, perceived advantages and risks. Methods Online questionnaire c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…A recent qualitative study of current and former IQOS users in the United Kingdom found that one of the main reasons for initiating HTP use and continued use was because it is 'less harmful', 'less hazardous', and 'less damaging' for their health than cigarettes [24]. A cross-sectional online survey of HTP users from various countries, mainly from Switzerland, reported 89% of respondents were using HTPs because they are less toxic than cigarettes [25]. Two other research studies in Korea [26] and Germany [27] also reported HTP use was positively associated with believing that they were less harmful than cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative study of current and former IQOS users in the United Kingdom found that one of the main reasons for initiating HTP use and continued use was because it is 'less harmful', 'less hazardous', and 'less damaging' for their health than cigarettes [24]. A cross-sectional online survey of HTP users from various countries, mainly from Switzerland, reported 89% of respondents were using HTPs because they are less toxic than cigarettes [25]. Two other research studies in Korea [26] and Germany [27] also reported HTP use was positively associated with believing that they were less harmful than cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Most users found IQOS weaker on the throat than combustible cigarettes and reported improved physical health, but feared becoming dependent. 28 …”
Section: Introductionmentioning
confidence: 99%
“…Most research on consumer responses to IQOS has been conducted by PMI 22–25. Independent survey research found that IQOS is perceived as less harmful than smoking 26–28. Focus group studies in Switzerland and Japan found IQOS was more socially acceptable, cleaner and uptake was encouraged by ‘clean and chic’ marketing and less of a harsh feeling on the throat compared with cigarettes 29.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Awareness of e-cigarettes and ecigarette experimentation have doubled both among adults and adolescents in many countries since 2008 (Grana, Benowitz, & Glantz, 2014). E-cigarette use has increased over time, especially among smokers to reduce their consumption of traditional tobacco products or to quit smoking (Queloz & Etter, 2019). Nonetheless, a recent study showed that e-cigarettes may have a higher addictive potential than smoked cigarettes (Jankowski et al, 2019).…”
Section: Introductionmentioning
confidence: 99%